Waren Judas en Thomas gnostici? Het evangelie naar Johannes met gnostische ogen gelezen - Beek, Abraham van de (HTS teologiese studies, 2008)
Jude and Thomas, were they Gnostics? Reading the Gospel according to John from a Gnostic perspective The discoveries of Gnostic texts since the mid of the twentieth century challenge biblical scholarship to read New Testament texts from new points of view. It is remarkable that Jesus’ disciples who are prominently present in Gnostic texts, especially Jude, Thomas and Philip are also more conspicuous characters in the Gospel of John than in the Synoptics. This challenges scholars to read these sections in relation to Gnosticism. The article aims at reading the scenes dealing with Jude and Thomas in John’s gospel with a Gnostic framework in mind. These texts gain more profile than by a traditional reading which is often based on a psychological understanding of Jude and Thomas. The article demonstrates that the author of John’s gospel uses these passages in an anti-Gnostic discourse. Thomas is a Gnostic who could fully understand Jesus’ words in a Gnostic way until he encounters the bodily risen Lord. Jude does not make such a conversion and disappears in the night. These are the option for Gnostics: either convert to the type of Christianity the Gospel of John teaches or being lost in darkness.